"A poem is a communicative act" : Exploring how speech acts in poetry convey writer intention - Sabure, Joadan (My University, 2025)
This thesis analyses the illocutionary acts in Frank O’Hara’s and Langston Hughes’ poetry. The purpose of the analysis is to examine how the complexities of speech acts present in natural dialogue can also be found in poetry, and to make an early case for pragmatically annotated, specific type of corpora of poetry that can partially fill the gap of the small number of pragmatically annotated corpora currently available for the study of speech acts. The analysis is conducted using speech act theory and the DART speech-act taxonomy. The three poems were analysed four times using the traditional speech act theory and once using the DART taxonomy. The analyses were done on paper and the illocutionary acts marked next to the poems. The results indicate that many of the speech acts used in everyday speech can also be found in poetry, having the same purpose and intention. Moreover, the results show that multiple speech acts can be in use simultaneously in an utterance. Finally, the analysis suggests that there exist many speech acts that are used by speakers but are yet to be named and categorized, and that poetry could potentially help with the exploration, categorization and naming of new speech acts for further research.
Keywords: speech act theory, DART speech-act taxonomy, poetry analysis